Pembinaan Prestasi Cabang Olahraga Muaythai di Kabupaten Grobogan Tahun 2022 - Az Zahra, Sandra Aina; Setiawan, Ipang (Indonesian Journal for Physical Education and Sport, 2023)
Muaythai sports in Grobogan District have achieved good achievements at the regional, national and international levels. The aim of the research is to describe the fostering of muaythai sporting achievements in Grobogan Regency. This research uses a qualitative descriptive approach. Collecting data using the method of observation, interviews, and documentation. Data analysis includes data collection, data reduction, data presentation and data verification. The results of the study show that achievement coaching is going well. Massaging is done by direct and indirect interaction. Nurseries are carried out by outreach at schools or visiting martial arts gyms in the region or outside the region. Sports actors are good, coaches have national licenses, athletes have achievements and management is going well. The training program is sufficient because it is structured. Facilities and infrastructure are still lacking. There are awards in the form of bonuses and incentives for athletes and coaches. From the results of the study it can be concluded that the implementation of achievement coaching is going well from the aspects of promotion, achievement, coaching, sports actors, infrastructure, funding and awards. The advice given is that the training program needs to be prepared and complete the lacking facilities.